Digital transformation of social security administration and services: A comparative analysis of Australia, Canada, Denmark and France (International Labour Organization (ILO), 2023)
The digital transformation of social security administration and services is complex and multifaceted. It requires careful consideration of various factors, such as the legal and regulatory frameworks, technological infrastructure, and social and cultural norms. This comparative analysis examines the digital transformation of social security administration and services in four countries - Australia, Canada, Denmark, and France - and identifies the key drivers, challenges, and key lessons learned. The comparison finds that the four countries have adopted different approaches to digital transformation, reflecting their unique political, economic, and social contexts. However, some common themes and trends emerge from the analysis. Two key drivers are identified in all four countries. The first driver of digital transformation is motivated by a desire to improve the efficiency and effectiveness of social security administration and services. This is particularly important as populations are ageing, demand for social services is rising, and competition for limited public sector resources is increasing. The innovative application of technology is opportunities to streamline processes, improve productivity and reduce costs while enhancing the quality of services. A second driver is a desire to enhance the quality of services and expansion. Digital technologies can enable more personalized and responsive services, as well as provide users with greater control over their data and interactions with social security agencies, and user experience and increase citizen engagement. From an initial focus on economic efficiencies, the four countries combined this with a desire to improve the user experience, increase user engagement in creating and testing new services, and include new beneficiaries. These drivers are enabled by a number of facilitating factors, including inter-agency and cross-governmental governance, coordination models setting and monitoring the strategic direction of the digital transition. The legal and regulatory framework and the associated standards facilitating efficient identity management, system interoperability and data exchange are key enablers, as are design, usability and accessibility standards for all public sector service solutions, websites, portals and apps. The service production and delivery ecosystems may be unique to each country. Still, they are all anchored in a network of specialized and unified service portals enabled by standards, system integration and connectivity, data exchange, electronic identities and signatures. Similarly, all countries actively address public sector capacities for technology to encourage innovation and change management - but in combination with traditional capacities and activities such as administrative burden reduction. A number of critical challenges to digital transformation are identified in the comparative anal ysis. Common to the four countries are concerns around data privacy and security, digital exclusion, and resistance to change from stakeholders such as employees, clients, and policymakers. These challenges require careful management and mitigation strategies to ensure that the benefits of digital transformation are realized while minimizing the risks. Similarly, data capture, management and quality assurance across service and organizational silos is a significant improvement area acknowledged in all four countries. Service and organizational silos continue to be a challenge. While consolidation, coordination and active collaboration are seen in both social security and the public sector service production and delivery ecosystems in all four countries. Federal countries like Australia and Canada are challenged by a relatively higher degree of fragmentation between central, regional and local authorities and service offers due to the national governance model. In comparison, France is challenged by more traditional public sector and social security silos. A cross-governmental, holistic and user-centric approach to digital transformation is thus crucial. Business and user needs and perspectives of all stakeholders are required but must balance the opportunities and risks of digital technologies. Anchored in the comparative analysis digital transformation of social security administration and services in Australia, Canada, Denmark and France, a set of key lessons can be synthesized: * Develop a clear vision and digital transformation strategy aligned with broader policy goals and stakeholder needs. Channel strategies, usability and active opt-out models facilitate the use of online services. * Build and continuously update a robust and adaptable technological infrastructure supporting a wide range of digital services and applications in an agile whole-of-government ecosystem. * Establish a digitization ready legal and regulatory framework, with regular impact assessment complemented with relevant standards and compliance mechanisms. * Establish clear data governance and quality assurance processes and apply once-only and single-sources of truth principles for data management and sharing. * Establish clear policies and guidelines around data privacy and security while ensuring appropriate safeguards are in place to protect sensitive information. * Engage with stakeholders, including clients, employees, policymakers, and other partners, to ensure that their needs and concerns are addressed and that they are involved in the design and implementation of digital services. * Provide training and support to employees and users to ensure they have the skills and knowledge to use digital services effectively. Build multi-faceted capacities to manage innovation, change and risk in organizations successfully. * Monitor and evaluate the impact of digital transformation on key outcomes, such as service quality, efficiency, and user satisfaction, and use this feedback to inform ongoing improvements and refinements. Link strategic objectives with operational performance indicators for benefits realization.
Keywords: 330; social security; social security administration